Methylprednisolone fails to attenuate lung injury in a mouse model of transfusion related acute lung injury. Issue 4 (27th August 2013) - Müller, Marcella C.A.; Tuinman, Pieter R.; van der Sluijs, Koenraad F.; Boon, Louis; Roelofs, Joris J.; Vroom, Margreeth B.; Juffermans, Nicole P.
<x xml:space="preserve">Abstract</x> Background Transfusion‐related acute lung injury (TRALI) is the leading cause of transfusion‐related morbidity and mortality. Anecdotally, TRALI patients have been treated with corticosteroids. However, evidence for its therapeutic rationale in TRALI is lacking. We determined the effects of corticosteroids on lung injury in a "two‐hit" mouse model of antibody‐mediated TRALI. Study Design and Methods BALB/c mice were primed with lipopolysaccharide, after which TRALI was induced by injecting major histocompatibility complex (MHC)‐I antibody against H2Kd. Mice infused with phosphate‐buffered saline served as controls. Simultaneously, one group of TRALI mice was infused with methylprednisolone (MPS; 2 mg/kg). Mice were supported by mechanical ventilation for 2 hours, after which bronchoalveolar lavage fluid (BALF) and lung homogenate were obtained. Statistics were obtained by one‐way analysis of variance or Kruskal‐Wallis. Results Injection of MHC‐I antibodies resulted in TRALI, indicated by pulmonary edema and increased BALF levels of protein and the proinflammatory mediators macrophage inflammatory protein‐2, keratinocyte‐derived chemokine, and interleukin (IL)‐6. Administration of MPS did not affect the amount of edema nor pulmonary protein and chemokine levels. MPS reduced systemic inflammatory reaction as well as IL‐6 levels in the BALF. Conclusion In a two‐hit model of antibody‐mediated TRALI, MPS attenuated the IL‐6 host response, but failed to prevent the development of lung injury.